Hydropower-economic Relationship between Nepal and India - Pandey , Lekha Nath; Patodiya, Pawan Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Nepal is an important actor in regional energy strategy because of its enormous water resources and great hydropower potential, which is projected to be over 83,000 megawatts. Nepal is located in the Himalayas, which puts it in a highly advantageous location. Because India’s rising energy demands create a major market for Nepal’s untapped hydropower potential, the economic relationship between Nepal and India is of the utmost importance. On the other hand, the development of these resources is not without its challenges, which include political instability, finance dependencies, and environmental issues, all of which have traditionally stymied progress. The study examines the strategic importance of hydropower not only in meeting energy needs but also as a geopolitical lever within the broader regional dynamics, especially considering the influences of neighbouring countries like China. Recent initiatives such as the Power Trade Agreement and cross-border electricity transmission projects underscore a renewed focus on enhancing cooperation, yet the realization of the full potential of this partnership requires addressing both technical and socio-economic challenges. Through a comprehensive review of governmental reports, policy documents, and academic literature, the study aims to provide a deeper understanding of the mechanisms that can foster sustainable and equitable growth in the hydropower sector, proposing pathways to overcome the current barriers. This analysis highlights the critical need for transparent and fair practices that can transform Nepal-India hydropower resources into a cornerstone for sustainable economic growth and regional stability, ensuring mutual benefits and long-term cooperation between the two nations.